Efektivitas Penerapan Model Pembelajaran Inkuiri Terbimbing Berbantuan Video Terhadap Hasil Belajar Fisika Peserta Didik Kelas X ATP 3 SMK Negeri 1 Gelumbang - Dina Andhayani (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2024)
This study is a pre-experimental study with a one-group pretest-posttest design conducted at SMK Negeri 1 Gelumbang aimed to (1) determine the extent of improvement in physics learning outcomes of students after the implementation of guided inquiry learning models (2) determine the effectiveness of guided inquiry learning models assisted by video in improving physics learning outcomes. The population in this study was students of class X ATP (Plantation Agribusiness) 3 totaling 28 students with a sample of 25 students. The data collection technique used was a learning outcome test consisting of 3 essay questions. Classroom Action Research (CAR) consisted of 2 cycles. Data in this study were obtained from teachers (observers) and students through observation, tests, and documentation. Based on the research data, the average value of physics learning outcomes before the implementation of guided inquiry learning models in cycle 1 was 34.80 and after being taught using guided inquiry learning models was 66.38. The N-Gain analysis obtained was 0.49, which is in the moderate category, with an interpretation of the N-Gain score percentage of 49% interpreted as less effective. Meanwhile, in cycle 2, there was an increase with an average of 51.20 becoming 89.20 with an N-Gain score of 0.79 or 79% which is in the high category and effective interpretation. From the analysis results in cycles 1 and 2, it can be concluded that the guided inquiry learning model assisted by video is effective in improving the physics learning outcomes of students.